LEARNING STRATEGIES AND GENDER DIFFERENCES IN ENGLISH GRAMMAR MASTERY: A COMPARATIVE STUDY OF THE EIGHTH GRADE STUDENTS AT SMP NEGERI 03 SELUMA - Eliza, Yola; Rizal , Syamsul; Haryanto , Endang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Grammar mastery is an important aspect of English language learning. The purpose of this study is to identify the Grammar Learning Strategies (GLS) used by male and female students, describe their grammar mastery, and determine whether there are significant differences in grammar mastery between male and female students. This study employed a quantitative comparative design with 81 eighth-grade students. Data were collected through a Grammar Learning Strategies Questionnaire and a Grammar Test, then analyzed using descriptive statistics and an independent samples t-test. The results of the study indicate that both male and female students use all categories of grammar learning strategies, with cognitive strategies being the most frequently used. The average score for grammar proficiency was 53.88 for male students and 53.89 for female students, indicating a low level of grammar proficiency. The results of the independent samples t-test showed a Sig. (two-tailed) value of 0.997 (> 0.05), indicating that there was no significant difference in English grammar proficiency between male and female students. Therefore, the null hypothesis (H₀) was accepted and the alternative hypothesis (Ha) was rejected.